The legal compliance of penalties imposed by specialty medical societies - Carlos Victor Silva Paixão (Revista Brasileira de Cirurgia Plástica)
Introduction: The study developed hereafter proposes to analyze the penalties imposed by Societies of Medical Specialties, entities organized in the form of civil associations, specially if they constitute legal usurpation of the competence of Professional Councils. The nature of these punishments and their effects and scope will be investigated, in order to verify whether there is effective damage to the professional practice of medicine by physicians. Methods: For this analysis, the applicable rules within the Brazilian legal system were raised, their systematization and apparent conflicts, in order to locate the associative punishments and their compliance with the current legal order. Results/Conclusion: It was verified from the study that there is no obstacle to the application of this type of sanctions, once the legal and constitutional guarantees of ample defense, contradictory and due process are respected.